The tyranny of timespace: examining the timetable of schooling activities as the interface between policy and everyday rhythms - Muller, Sara (School of Education, 2020)
This thesis seeks to understand the role of school timetables as an interface between policies that regulate or distribute forms of capital to schools, and their teaching and learning rhythms. By doing so, it proposes a mechanism for examining the reproduction of schooling practices, and how these are grounded in policy-regulated materiality. Two high schools with similar historic backgrounds, and operating under the same provincial government, were selected and closely studied for evidence of rhythms of practice and the correspondence of these rhythms to each school's timetable. The two schools now experience different access to resources, and have significant differences in teaching and learning rhythms, as well as school-leaving summative assessment results. The study develops an analytic framework for identifying policies that reach into schools through the timetable. Five key inputs are identified as necessary for constructing timetables, providing productive lines of inquiry as to which policies affect schooling rhythms and how. By asking who teaches whom, what, with what and where, systematic analysis is conducted on: how schools are staffed (who); who they enrol (whom); their interpretation of curriculum (what); what supplementary resources they can command (with what); and their infrastructural facilities and geographic (dis)advantages (where). The interaction between these different threads is examined as they tangle within each school's timetable. The enactment of the policies regulating each thread is then traced through the layers of governance of the South African education system: national, provincial and local (school-level). Timetables are conceptualised in this study as local representations of intended teaching and learning rhythm. Using Lefebvre's triad of timespace-conceived, timespace-perceived and timespace-lived, timetables (timespace-conceived) are brought into conversation with timespace-lived through daily teaching and learning activities. Bourdieu's theory of practice is used with Lefebvre to animate the ‘game' of schooling: what schools strive for, what forms of capital they can command to sustain or improve their field position, and how they reproduce their practices. Bourdieu and Lefebvre together generate a sociomaterial practice theory lens that foregrounds timetables and their legitimacy to govern rhythms of teaching and learning in timespace. Timetables emerge as a site of the production and reproduction of advantage (fortified schools) and/or disadvantage (exposed schools) in the game of schooling. In timetables, the policies that avail forms of capital interact in previously unconsidered ways, suggesting that collectively they potentially undergird inequality in the education system.